Analisa Pasal 53 KHI Tentang Pelaksanaan Kawin Hamil Diluar Nikah Ditinjau Dari Hukum Islam - Haeratun - (Fakultas Hukum Universitas Mataram, 2015)
Mafsadat opportunities contained in article 53 of KHI because of the obscurity limits allowed because pregnancy made her pregnant mate in article 53 KHI. The impact is not uncommon to Article 53 KHI made pregnant as a result of adultery legality mating. This is clearly not in accordance with Islamic law strictly prohibits the practice of adultery. To analyze these problems, in this study the two proposed formulation of the problem which is how the view of Islamic law to the formulation of Article 53 of the KHI and the factors that encourage pregnant mating society, to eliminate aspects mafsadat in article 53 of KHI, in the context of al-dzari saddu 'at, the necessary editorial changes such as the addition of boundary conditions cause pregnancy and accompanying sanctions. The formulation of Article 53 KHI as pregnant kwin solution can be realized by adding the editorial-related restrictions that can cause pregnant mating carried out in the absence of sanctions and sanctions for pregnant mating caused adultery form of social repentance.